Pengembangan Media Video Interaktif Berbasis Edpuzzle pada Materi Sistem Pencernaan Manusia Kelas 8D SMP Islam Al Fattahiyyah - Kamalin, Azza Niela; Rozi, Fahrur (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to develop an interactive video-based learning media using Edpuzzle for teaching the human digestive system to 8D grade students at SMP Islam Al Fattahiyyah. The research was motivated by the low student engagement and the lack of interactive learning tools that actively involve students in science education, particularly in the digestive system topic. This study employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection instruments included expert validation questionnaires (media and content experts) and student response assessments. The validation results showed that the Edpuzzle-based interactive video media is highly feasible, with an average score of 92% from media experts, 89% from content experts, and 91% from student responses. These findings indicate that the developed media not only improves students' conceptual understanding but also enhances active student participation in the learning process. In conclusion, the Edpuzzle media is suitable as an innovative alternative in science learning, particularly for teaching the human digestive system at the junior high school level.